2010
DOI: 10.1186/cc8451
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new tracheostomy technique for morbidly obese patients on an intensive care unit

Abstract: IntroductionWe previously showed that erythropoietin (EPO) attenuates the morphological signs of spinal cord ischemia/reperfusion (I/R) injury in swine [1] without, however, improving neurological function. The clinical use of EPO has been cautioned most recently due to serious safety concerns arising from an increased mortality in acute stroke patients treated with EPO and simultaneously receiving systemic thrombolysis [2]. Carbamylated EPO (cEPO) is an EPO derivative without erythropoietic activity and devo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Twelve studies included a comparison group without obesity, 4,10,[23][24][25][26][27][28][29][30][31][32] 1 study compared PDTs with OSTs in patients with obesity, 33 and the remaining 5 studies reported solely on PDT outcomes in patients with obesity. [34][35][36][37][38] Table 1 summarizes the study design, included patients, and surgical technique, while Table 2 presents the PDT-associated complication rates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twelve studies included a comparison group without obesity, 4,10,[23][24][25][26][27][28][29][30][31][32] 1 study compared PDTs with OSTs in patients with obesity, 33 and the remaining 5 studies reported solely on PDT outcomes in patients with obesity. [34][35][36][37][38] Table 1 summarizes the study design, included patients, and surgical technique, while Table 2 presents the PDT-associated complication rates.…”
Section: Resultsmentioning
confidence: 99%
“…The mortality rate in the 15 included studies reporting mortality directly associated with the procedure in individuals with obesity was 0.3% (2 of 727 patients). 4,10,[23][24][25][26]28,29,31,[33][34][35][36][37][38] One patient had a cardiac arrest during a Griggs PDT after having recurrent episodes of ventricular fibrillation in the context of a coronary artery bypass graft requiring intraaortic balloon counterpulsation, while another died the day after PDT from massive hemorrhage secondary to an unidentified subcutaneous vessel. 24…”
Section: Mortality Directly Associated With the Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…1). 4 Emergency cricothyrotomy in a 'cannot intubate, cannot ventilate' scenario is also potentially more difficult due to increased neck circumference and thickness of subcutaneous tissues, which distorts anatomical landmarks. Cannula cricothyrotomy is considered preferential to needle cricothyrotomy in this group of patients, although evidence supporting one technique over another is limited.…”
Section: Tracheostomy Proceduresmentioning
confidence: 99%